The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1528-1157.2002.32501.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron Status: A Possible Risk Factor for the First Febrile Seizure

Abstract: Summary:Purpose: We conducted a controlled study to investigate the relation of iron status and first febrile seizure (FFS).Methods: Measures of iron sufficiency including hemoglobin concentration (HB), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and plasma ferritin (PF) were prospectively measured in 75 children with FFS and compared with 75 controls matched for age and sex with febrile illnesses without convulsions.Results: Mean ferritin level was significantly lower in cases with FFS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
115
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(139 citation statements)
references
References 15 publications
18
115
4
2
Order By: Relevance
“…Respiratory tract infection was the most commonly observed probable illness, as a cause for fever. This was also seen in studies by Piscane et al, Daod et al and Srinivasa et al 13,19,23 Malaria was the common infection found in Idro et al in about 67%. Temperature at time of admission in cases was not found statistically significant in present study though it was significant in Piscane et al (p-value of 0.000) and in Bidabadi et al (p-value of <0.001).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Respiratory tract infection was the most commonly observed probable illness, as a cause for fever. This was also seen in studies by Piscane et al, Daod et al and Srinivasa et al 13,19,23 Malaria was the common infection found in Idro et al in about 67%. Temperature at time of admission in cases was not found statistically significant in present study though it was significant in Piscane et al (p-value of 0.000) and in Bidabadi et al (p-value of <0.001).…”
Section: Discussionsupporting
confidence: 66%
“…Daod et al Piscane et al and Fallah et al also found serum ferritin to be statistically correlating with febrile seizures. 13,19,27 Vaswani et al, Kumari et al among Indian studies have reported the same correlation between febrile seizures and serum ferritin levels. 17,20 In studies by Bidabadi et al, Yousefchaijan et al and Idro et al, patients did not show any statistical correlation between ferritin levels and febrile convulsions.…”
Section: Discussionmentioning
confidence: 64%
“…19 Similar results were observed by Pisacane, et al Daoud, et al showed mean serum ferritin was significantly low in children with first febrile seizure and also proportion of children with low ferritin was significantly higher in febrile seizure group than in controls. 4,20 Some studies done in India also agrees with these findings. 9,21 One finding which stands unique in our study Serum Iron which is less in case group which shows that iron deficiency can have positive association with febrile seizures.…”
Section: Discussionsupporting
confidence: 65%
“…So, the difference is statistically significant i.e significant number of the cases had low serum ferritin level in comparison to controls. Daoud et al 8 mentioned that mean ferritin level were lower in children who had a seizure with fever, suggesting a possible risk factors in febrile seizures. They have shown that the mean plasma ferritin level was significantly lower (p <0.0001) in the first febrile seizure group compared to the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their association with epilepsy in future in some cases, various studies have attempted to identify the risk factors associated with FS like family history of FS or epilepsy, perinatal factors like maternal smoking & alcohol consumption 3 . Among several other risk factors iron deficiency has been found as a provocating factor of FS in different studies 4,5 .…”
Section: Introductionmentioning
confidence: 99%